A Database of Diseases of Medicinal Plants in Uttarakhand - Bhandari, Shubhra; Harsh, N. S. K.; Sharma, A. K.; Puni Mao, L.; Thakur, Shikha (Indian Forester, 2014)
Medicinal plants play an important role in the development of potent therapeutic agents. Now-a-days large scale and commercialized cultivation has increased the number of diseases and their severity in medicinal plants. Among the bioagents fungal phytopathogens are found to cause certain foliar diseases which eventually play an important role in affecting overall health of the medicinal plants and their products. In the present study information about diseases of medicinal plants of Uttarakhand has been compiled to prepare a database.